Environmental Stability and Infectivity of Hepatitis C Virus (HCV) in Different Human Body Fluids - Pfaender, Stephanie; Helfritz, Fabian A.; Siddharta, Anindya; Todt, Daniel; Behrendt, Patrick; Heyden, Julia; Riebesehl, Nina; Willmann, Wiebke; Steinmann, Joerg; Münch, Jan; Ciesek, Sandra; Steinmann, Eike (Frontiers in Microbiology, 2018)
Background. Hepatitis C virus (HCV) is a hepatotropic, blood-borne virus, but in up to 1/3 of infections the transmission route remained unidentified. Viral genome copies of HCV have been identified in several body fluids, however, non-parental transmission upon exposure to contaminated body fluids seems to be rare. Several body fluids, e.g. tears and saliva, are renowned for their antimicrobial and antiviral properties, nevertheless, HCV stability has never been systematically analysed in those fluids. Methods. We used state of the art infectious HCV cell culture techniques to investigate the stability of HCV in different body fluids to estimate the potential risk of transmission via patient body fluid material. In addition, we mimicked a potential contamination of HCV in tear fluid and analyzed which impact commercially available contact lens solutions might have in such a scenario. Results. We could demonstrate that HCV remains infectious over several days in body fluids like tears, saliva, semen and cerebrospinal fluid. Only hydrogen-peroxide contact lens solutions were able to efficiently inactivate HCV in a suspension test. Conclusions. These results indicate that HCV, once it is present in various body fluids of infected patients, remains infective and could potentially contribute to transmission upon direct contact.